Cymbeline, King of Britain - "Shakespeare, William" (Sweet cherry publication: China, 2013)
Cymbeline, King of Britain is one of the best-known works of William Shakespeare. It is a romantic play interwoven with war and tragedy. It revolves around Cymbeline and his daughter, Imogen. Imogen does not abide by her father s wishes, and marries a lowborn gentleman, Posthumous. After their marriage, Posthumous is banished from Britain and Imogen is held as a prisoner in the palace. As the play unfolds, the evil plots of the queen, Imogen s stepmother, the jealousy of Posthumous and the loyalty of Imogen come to light. This short narrative version of the play has been suitably adapted to help introduce the play to young readers. It can be read by children or read to them by parents who wish to introduce them to the play
Keywords: Adaptations Juvenile literature